Neurosensory and Cognitive Modifications in Europe's Toughest RandoRaid Competition: the Transpyrénéa Extreme Study - Tonacci, Alessandro; Mrakic-Sposta, Simona; Ujka, Kristian; Sansone, Francesco; Ferrisi, Alice; Giardini, Guido; Conte, Raffaele; Pratali, Lorenza (Frontiers in Physiology, 2017)
Introduction: Given the wide proliferation of ultra-long endurance races, it is important to understand the physiological response of the athletes to improve their safety. We evaluated the cognitive and neurosensory effects on ultra-endurance athletes during the Transpyrénéa (866 Km, 65,000 m positive slope), held on the French Pyrenees. Materials and Methods: 40 athletes were enrolled (age 43.8±8.8 years; 36 males). Olfactory and cognitive tests were performed before the race (T0, n=40), at 166 kms (T1, n=28), at 418 kms (T2, n=20) and after the race (T3, 866 kms, n=13). The effect of dehydration and sleep deprivation on cognitive features were also studied. Results: Olfactory function decreased during the race (T0: 24.9±4.3 vs T3: 22.8±3.5, z=-2.678, p=0.007), language fluency increased (T0: 10.8±2.9; T1: 11.4±2.7; T2: 12.9±2.8; T3: 12.9±3.0; χ2=11.132, p=0.011 for combined samples), whereas the Trail Making Test did not show any changes between pre- and post-race (T0 vs T3 p=0.697 for TMT-A, p=0.977 for TMT-B). The mean aggregate sleeping time was 9.3±5.4 h at T1, 22.4±10.0 h at T2, 29.5±20.5 h at T3, with a correlation with olfactory function(r=0.644, p=0.018), while Total Body Water (TBW) was not correlated with olfactory or cognitive scores. Conclusion: Physical activity and sleep restriction in ultra-endurance could transiently affect olfactory function, while verbal fluency improved, demonstrating a dissimilar mechanism of activation/deactivation in different cortical areas. Body water loss was uncorrelated to cognition. Further studies should clarify whether cognitive and sensory deficits occur even in absence of sleep restriction.